Hepatic Steatosis, Carbohydrate Intake, and Food Quotient in Patients with NAFLD - Concepcion Gonzalez; Victor de Ledinghen; Julien Vergniol; Juliette Foucher; Brigitte Le Bail; Sabrina Carlier; Elisa Maury; Henri Gin; Vincent Rigalleau (International Journal of Endocrinology)
Is steatosis related to the spontaneous carbohydrate intake in patients with NAFLD? We performed dietary records for 24 patients with NAFLD, 3 months after their liver biopsy was performed and before the deliverance of a dietary advice. The food quotient, indicator of the proportion of calories from carbohydrates, was calculated as (1.00×%  calories from carbohydrates/100) + (0.70×%  calories from lipids/100) + (0.81×%  calories from proteins/100). The associations between diet variables and steatosis% on the hepatic biopsies were tested by regression analysis, and diet variables were compared according to the presence of fibrosis. The subjects displayed a large range of steatosis, 50.5% ± 25.5 [10–90], correlated with their energy intake (1993 ± 597 kcal/d, , ) and food quotient (0.85 ± 0.02, , ), which remained significant with both variables by a multivariate regression analysis (, ). For the 17/24 patients with a hepatic fibrosis, the energy intake was lower (fibrosis: 1863 ± 503 versus others: 2382 ± 733 kcal/d, ), and their food quotients did not differ from patients without fibrosis. Hepatic steatosis was related to the energy and carbohydrate intakes in our patients; the role of dietary carbohydrates was detectable in the range of usual carbohydrate intake: 32% to 58% calories.